Nutritional diagnosis of ‘Montenegrina’ mandarin orchards at the southern Brazil - Griebeler, Sabrina Raquel; Pereira Gonzatto, Mateus; Schwarz, Sergio Francisco; Böettcher, Gerson Nestor; Fernandes Pauletti, Gabriel; Duarte Rota, Luciana (Revista Ceres, 2023)
The correct nutrition of orchards from fertilizer management directly influences fruit yield. Therefore, the objective was to evaluate the nutritional status of orchards of the ‘Montenegrina’ mandarin (Citrus deliciosa Tenore) grafted on Poncirus trifoliata Raf. in southern Brazil. The study included analyzes of soil and leaf tissue from 58 commercial orchards. More than 60% of the orchards were diagnosed with K and Mg insufficiency and more than 30% had an excess of N. There was an insufficiency in Mn and Zn of 60 and 96%, respectively, despite the levels of these micronutrients in the soil being high in both depths studied. In addition, no significant correlations were observed between the contents of a given nutrient in the soil and in the leaves, except for the Ca/Mg ratio. Insufficiency was observed in the leaf contents of K, Mg, Mn and Zn and excesses of N and Cu in the orchards. The use of phosphate and potassium fertilizers requires adjustments due to the excessive content of these nutrients in the soil. Pre-planting acidity correction and soil acidity management in ‘Montenegrina’ mandarin orchards already implanted needs to be optimized.